“You Avenge the Others”: The Portrait of a Femme Fatale in Gladys Huntington’s Madame Solario - Piechucka, Alicja (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The article deals with the concept of femme fatale as presented in Gladys Huntington’s 1956 novel Madame Solario. The eponymous protagonist, Natalia Solario, displays several characteristics of this female archetype, omnipresent in literature, culture and visual iconography. As a femme fatale, Natalia is beauty, danger and mystery incarnate. The cause of tragedies, but also a tragic figure herself, Madame Solario is both victim and victimizer. The article explores the interplay between innocence and experience, life and death, the erotic and the thanatic, as well as the motifs of transgression, ambiguity, love, passion, desire, perversion, dominance and control crucial to Huntington’s novel. Madame Solario reminds us that, paradoxically, the femme fatale usurps certain stereotypically masculine traits. This, in turn, brings us to the novel’s feminist dimension: the femme fatale is victimized by men, but she is also the agent of female revenge and, ultimately, liberation, symbolically marking the transition from patriarchy to women’s emancipation.